Liver transplantation, adolescence and transition to adults’ clinic - Bermudez, Beatriz Elizabeth Bagatin Veleda; Weber, Lídia Natália Dobrianskyj; Parolin, Mônica Beatriz; Coelho, Júlio Cezar Uilli; Bermudez, Mariane Bagatin; Celli, Adriane (Brazilian Journal of Transplantation, 2010)
Purpose: Provide information to hepatologists on the care of adolescent transplant recipients and how they can collaborate by adhering to immunosuppressive treatment to avoid risk of rejection as well as focusing other important issues of adolescence. Data source: Information was collected from scientific articles published on SciELO, MEDLINE, and PubMed databases from 2004 to 2010, books and papers from articles of consensus of international agencies. Data synthesis: As a result of the increasing amount of transplants as well as the survival improvement, many transplanted children are attaining the turbulent adolescence period. Few transplant services have standardized a transition program to assure an adequate health’s follow-up for adolescent patients after their transfer to an adult clinic. Some authors state that attention during such transitional period provides a review of education for adolescent patients as well as an opportunity to optimize the well-being in adulthood. Unfortunately, general clinics for adults are overwhelmed of patients, and the adolescent’s development issues are not priorities. The pediatrician, who should be essential in transferring adolescents to adult health services, often unconsciously act as a complicating factor, since they do not show fully confident on his colleagues. Conclusion: The outpatient transition can provide opportunity to address essential issues for the overall well-being and health to adolescent liver transplant patients as well as focusing important points for their full development, including their autonomy, identity, self-esteem, quality of life, sexuality, body changes, life projects and educational / professional development.